Contribution of spinal cord biopsy to diagnosis of aquaporin-4 antibody positive neuromyelitis optica spectrum disorder. (June 2014) - Ringelstein, M; Metz, I; Ruprecht, K; Koch, A; Rappold, J; Ingwersen, J; Mathys, C; Jarius, S; Brück, W; Hartung, H-P; Paul, F; Aktas, O; et al.
Longitudinally extensive transverse myelitis is characteristic but not pathognomonic for neuromyelitis optica spectrum disorders (NMOSDs) and may mimic local tumors. In this retrospective study based on a cohort of 175 NMOSD patients we identified seven patients who initially presented with a longitudinally extensive spinal cord lesion and underwent spinal cord biopsy due to magnetic resonance imaging (MRI)-suspected malignancies. Remarkably, routine neuropathology was inconclusive and did not guide the diagnostic process to anti-aquaporin-4 (AQP4)-seropositive NMOSD. Serious postoperative complications occurred in 5/7 patients and persisted during follow-up in 2/7 patients (29%). Considering these sequelae, AQP4-antibody testing should be mandatory in patients with inconclusive longitudinally extensive spinal cord lesions prior to biopsy.